In vitro chondrogenic commitment of human Wharton's jelly stem cells by co‐culture with human articular chondrocytes. (7th September 2015) - Pereira, R. C.; Costa‐Pinto, A. R.; Frias, A. M.; Neves, N. M.; Azevedo, H. S.; Reis, R. L.
Abstract: Wharton's jelly stem cells (WJSCs) are a potential source of transplantable stem cells in cartilage‐regenerative strategies, due to their highly proliferative and multilineage differentiation capacity. We hypothesized that a non‐direct co‐culture system with human articular chondrocytes (hACs) could enhance the potential chondrogenic phenotype of hWJSCs during the expansion phase compared to those expanded in monoculture conditions. Primary hWJSCs were cultured in the bottom of a multiwell plate separated by a porous transwell membrane insert seeded with hACs. No statistically significant differences in hWJSCs duplication number were observed under either of the culture conditions during the expansion phase. hWJSCs under co‐culture conditions show upregulations of collagen type I and II, COMP, TGFβ1 and aggrecan, as well as of the main cartilage transcription factor, SOX9, when compared to those cultured in the absence of chondrocytes. Chondrogenic differentiation of hWJSCs, previously expanded in co‐culture and monoculture conditions, was evaluated for each cellular passage using the micromass culture model. Cells expanded in co‐culture showed higher accumulation of glycosaminoglycans (GAGs) compared to cells in monoculture, and immunohistochemistry for localization of collagen type I revealed a strong detection signal when hWJSCs were expanded under monoculture conditions. In contrast, type II collagen was detected when cells were expanded under co‐culture conditions, where numerous round‐shaped cell clusters were observed. Using a micromass differentiation model, hWJSCs, previously exposed to soluble factors secreted by hACs, were able to express higher levels of chondrogenic genes with deposition of cartilage extracellular matrix components, suggesting their use as an alternative cell source for treating degenerated cartilage. Copyright © 2015 John Wiley & Sons, Ltd.